Validity and Reliability of the Thai Version of the Freezing of Gait Questionnaire in Individuals With Parkinson’s disease - Arisa Taweekitikul; Phakamas Tanvijit; Pheeravut Tantisuvanitchkul; Prachaya Srivanitchapoom; Yuvadee Pitakpatapee; Fuengfa Khobkhun; Piyapong Akkathep (Annals of Rehabilitation Medicine, 2023)
Objective To evaluate the validity and reliability of the Thai version of the Freezing of Gait Questionnaire (FOG-Q) in individuals with Parkinson’s disease (PD). Methods The FOG-Q was translated into Thai according to the standard process. Fifty-six individuals with PD participated in the study. The content validity was assessed using the content validity index (CVI). The construct validity was evaluated by correlating Thai FOG-Q with Thai version of the Movement Disorder Society-sponsored revision of the Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) items 2.13 and 3.11, Thai version of the Falls Efficacy Scale-International (FES-I), Timed Up and Go test (TUG) and Berg Balance Scale (BBS) using Spearman’s correlation coefficient (rS). The correlation between Thai FOG-Q and clinical characteristics, for example, duration of PD and modified Hoehn and Yahr (mH&Y) stage was evaluated. Internal consistency and test-retest reliability were evaluated with Cronbach’s alpha (Cα) and intraclass correlation coefficient (ICC), respectively. Results The Thai FOG-Q had high content validity (CVI=0.96). The mean FOG-Q score was 9.0±4.9. The construct validity showed a strong positive correlation with MDS-UPDRS item 2.13 (rS=0.81), and moderate correlations with MDS-UPDRS item 3.11, FES-I, and TUG (rS=0.42–0.60). A negative correlation with BBS was found (rS=-0.32). It had a moderate correlation with mH&Y stage (rS=0.40). The Thai FOG-Q had good internal consistency (Cα=0.87) with excellent test-retest reliability (ICC=0.91). Conclusion The Thai FOG-Q has excellent validity and reliability. It is a useful instrument for the evaluation of FOG in individuals with PD.